Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/acem.13241
|View full text |Cite
|
Sign up to set email alerts
|

Society for Academic Emergency Medicine Statement on Plagiarism

Abstract: The integrity of the research enterprise is of the utmost importance for the advancement of safe and effective medical practice for patients and for maintaining the public trust in health care. Academic societies and editors of journals are key participants in guarding scientific integrity. Avoiding and preventing plagiarism helps to preserve the scientific integrity of professional presentations and publications. The Society for Academic Emergency Medicine (SAEM) Ethics Committee discusses current issues in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Our patients, the clinicians who treat them, and the policymakers involved in various aspects of healthcare rely on credible, honest scholarship to inform decision-making. We agree also with the Society of Academic Emergency Medicine's (SAEM) recently published position statement that "the integrity of the research enterprise is of the utmost importance for the advancement of safe and effective medical practice for patients and for maintaining the public trust in health care" [2].…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…Our patients, the clinicians who treat them, and the policymakers involved in various aspects of healthcare rely on credible, honest scholarship to inform decision-making. We agree also with the Society of Academic Emergency Medicine's (SAEM) recently published position statement that "the integrity of the research enterprise is of the utmost importance for the advancement of safe and effective medical practice for patients and for maintaining the public trust in health care" [2].…”
mentioning
confidence: 54%
“…Earlier this year, the editor-in-chief of Annals of Internal Medicine reported that the reviewer of one of its manuscripts "had stolen the contents of a manuscript sent to that reviewer for evaluation" and then that reviewer published that very same content almost verbatim in another journal [11]. Although that is obviously an egregious and bold form of plagiarism, in today's world of electronically shared and distributed data, plagiarism runs the entire gamut from overt plagiarism of another's intellectual property (as in that Annals case) to patchwork plagiarism from various sources, including from oneself [2]. Regardless of how it happens, any form "plagiarism tarnishes the research integrity" [12].…”
mentioning
confidence: 99%
“…The aim was to inspect knoweldege and attitude of students towards plagiarism and to educate them to avoid plagiarism by means which are acceptable to achieve our objective. (6) The unethical act of using someone else's work as your own without or with the consent of a writer is plagiarism. Scientific writing is threatened for such transgressions since it constitutes literary robbery.…”
Section: Introductionmentioning
confidence: 99%
“…Disclosure of COI therefore aims to provide readers and other consumers complete context to make an informed judgment of the work . In published science, journal editors and peer reviewers serve as the first set of gatekeepers, but the onus is also on readers of journals to question findings and put a voice to those questions if something seems off …”
mentioning
confidence: 99%
“…Even different forms of plagiarism can meet the definition of a nonfinancial COI as described in an SAEM Position Statement published recently in this journal . In today's multimedia era where so much scholarship is disseminated and shared electronically, using another's intellectual property by copy‐and‐paste without appropriate attribution, listing colleagues as authors who do not meet the ICMJE standard for authorship, or even recycling one's own previous work may undermine the integrity of the scientific enterprise when done to advance a secondary personal interest …”
mentioning
confidence: 99%